Analisis SWOT dan Bisnis Model Kanvas (Studi Kasus Toko EKM Motor) - Erwin Kurniawan; Fransisca . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
Industry is an activity that starts from the processing of a raw materials / semi-finished materials into a finished product that has a value that is more useful so they can benefit. Based on BPS survey, such as the automotive industry is one industry that provides a substantial contribution to the economy of Indonesia amounting to Rp 275 trillion in 2013. Along with the development of technology as much as 20% of the total 74.6 million internet users in Indonesia do online shopping, the authors conducted a business development by opening an online store that sells automotive spare parts